Analisis Penetapan Mens Rea dan Unsur Sifat Melawan Hukum Materil dalam Kasus Korupsi Impor Gula Tom Lembong - Febrainy Nurphi (Jurnal Hukum Lex Generalis, 2026)
The Tom Lembong sugar import case blurs the boundaries between administrative discretion and corruption. This study analyzes the determination of mens rea after PMK 003/PUU-IV/2006. The results show that after PMK 003/PUU-IV/2006, mens rea must be proven cumulatively through the principle of willens en wetens. The perpetrator's knowledge and will must be proven to lead to corrupt intent, not simply an administrative error. In this case, malicious intent cannot be assumed from state losses, but rather there must be a causal relationship between the deliberate violation of procedures and the motive for illegal gain. In conclusion, a clear distinction between policy failure and malicious intent is crucial to prevent the criminalization of official discretion and ensure legal certainty for public officials.